2020
DOI: 10.1016/j.virusres.2020.198170
|View full text |Cite
|
Sign up to set email alerts
|

Signal hotspot mutations in SARS-CoV-2 genomes evolve as the virus spreads and actively replicates in different parts of the world

Abstract: Highlights Study of SARS-CoV-2 genomes from world-wide isolates. Sequence comparisons of 570 isolates to original Wuhan 2019 SARS-CoV-2 clade. Identification of several hotspot mutants after world-wide spreading of virus. Several hotspot mutations affect sequences of replication-relevant viral proteins. How do hotspot mutations relate to viral pathogenicity?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 16 publications
2
51
0
Order By: Relevance
“…We have summarised the polymorphism along with respective allele frequencies and amino acid consequences in Figure 1. Weber et al (2020) have interrogated 572 SARS-CoV-2 genomes isolated worldwide and characterised 10 distinct mutation hotspots that have been found in up to 80% of the viral genomes they examined [61]. While our reported variant positions are not 100 % in concordant with these hotspots, some of them display changes on or adjacent to our reported positions.…”
Section: Discussionmentioning
confidence: 49%
“…We have summarised the polymorphism along with respective allele frequencies and amino acid consequences in Figure 1. Weber et al (2020) have interrogated 572 SARS-CoV-2 genomes isolated worldwide and characterised 10 distinct mutation hotspots that have been found in up to 80% of the viral genomes they examined [61]. While our reported variant positions are not 100 % in concordant with these hotspots, some of them display changes on or adjacent to our reported positions.…”
Section: Discussionmentioning
confidence: 49%
“…Divergence of immune response might be a repercussion of viral mutations. Namely, several reports result showed that, due to SARS-CoV-2 rapidly spreading across countries, new mutation hotspots are emerging in different parts of the genome, indicating a presence of different viral strains in Europe and Asia, with European strains being more virulent [35][36][37][38]. Also, sex differences in monocyte subsets redistribution are described [39].…”
Section: Plos Onementioning
confidence: 99%
“…Researchers aimed too to analyse SARS-CoV-2 proteins modulating host immune response like type I interferon pathways ( Li et al, 2020b ). People have tried to uncover the relation between hotspot mutations and viral pathogenicity ( Weber et al, 2020 ). Some research papers focused on characterizing B and T cell epitopes of certain proteins of SARS-CoV-2 which can help in vaccine development ( Li et al, 2020c ).…”
Section: Introductionmentioning
confidence: 99%